Efektivitas Mindfulness Untuk Meningkatkan Kualitas Hidup - Ayu, Desak Ulan Sukmaning; Yudiarso, Ananta (Jurnal Psikologi Udayana, 2021)
Mindfulness is an intervention that has an influence on the quality of life of individuals. This study aims to measure and explain the effectiveness of providing mindfulness interventions to improve quality of life using a meta-analysis method through a literature review of 17 international research journals from 2008 to 2020 that are relevant to mindfulness and quality of life. Participants in the study was 1699 people divided into two groups: 871 people in the experimental group and 828 people in the control group. The results of data processing carried out by looking at the value of Mean (M), Standard Deviation (SD), and the number of samples (N) found on the effect size value from random effect model, which is equal to 0.161 (95% CI = 0.0 to 0.63, P = 0.049679) with I2 (inconsistency) = 89.0%. The meta-analysis test it can be concluded that mindfulness gives little effectiveness to the quality of life of individuals. This is because mindfulness interventions tend to affect psychological conditions related to quality of life.